Baricitinib for systemic lupus erythematosus: a double-blind, randomised, placebo-controlled, phase 2 trial. Issue 10143 (21st July 2018) - Wallace, Daniel J; Furie, Richard A; Tanaka, Yoshiya; Kalunian, Kenneth C; Mosca, Marta; Petri, Michelle A; Dörner, Thomas; Cardiel, Mario H; Bruce, Ian N; Gomez, Elisa; Carmack, Tara; DeLozier, Amy M; et al.
Summary: Background: Patients with systemic lupus erythematosus have substantial unmet medical need. Baricitinib is an oral selective Janus kinase (JAK)1 and JAK2 inhibitor that we hypothesised might have therapeutic benefit in patients with systemic lupus erythematosus. Methods: In this double-blind, multicentre, randomised, placebo-controlled, 24-week phase 2 study, patients were recruited from 78 centres in 11 countries. Eligible patients were aged 18 years or older, had a diagnosis of systemic lupus erythematosus, and had active disease involving skin or joints. We randomly assigned patients (1:1:1) to receive once-daily baricitinib 2 mg, baricitinib 4 mg, or placebo for 24 weeks. The primary endpoint was the proportion of patients achieving resolution of arthritis or rash at week 24, as defined by Systemic Lupus Erythematosus Disease Activity Index-2000 (SLEDAI-2K). Efficacy and safety analyses included all patients who received at least one dose of study drug. This study is registered with ClinicalTrials.gov, number NCT02708095 . Findings: Between March 24, 2016, and April 27, 2017, 314 patients were randomly assigned to receive placebo (n=105), baricitinib 2 mg (n=105), or baricitinib 4 mg (n=104). At week 24, resolution of SLEDAI-2K arthritis or rash was achieved by 70 (67%) of 104 patients receiving baricitinib 4 mg (odds ratio [OR] vs placebo 1·8, 95% CI 1·0–3·3; p=0·0414) and 61 (58%) of 105 patients receiving baricitinib 2 mg (OR 1·3, 0·7–2·3; p=0·39). Adverse events were reported in 68 (65%) patients in the placebo group, 75 (71%) patients in the baricitinib 2 mg group, and 76 (73%) patients in the baricitinib 4 mg group. Serious adverse events were reported in ten (10%) patients receiving baricitinib 4 mg, 11 (10%) receiving baricitinib 2 mg, and five (5%) receiving placebo; no deaths were reported. Serious infections were reported in six (6%) patients with baricitinib 4 mg, two (2%) with baricitinib 2 mg, and one (1%) with placebo. Interpretation: The baricitinib 4 mg dose, but not the 2 mg dose, significantly improved the signs and symptoms of active systemic lupus erythematosus in patients who were not adequately controlled despite standard of care therapy, with a safety profile consistent with previous studies of baricitinib. This study provides the foundation for future phase 3 trials of JAK1/2 inhibition with baricitinib as a new potential oral therapy for systemic lupus erythematosus. Funding: Eli Lilly and Company.